2020
DOI: 10.3390/su122410548
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Compressive Behaviour of Sustainable Cement-Based Composites under One-Hour of Direct Flame Exposure

Abstract: Fire is a significant threat to human life and civil infrastructures. Builders and architects are hankering for safer and sustainable alternatives of concrete that do not compromise with their design intent or fire safety requirements. The aim of the present work is to improve the residual compressive performance of concrete in post-fire exposure by incorporating by-products from urban residues. Based on sustainability and circular economy motivations, the attention is focused on rubber tire fly ash, aged bric… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…To increase the fire resistance of structure is considered to do various methods of protection of beam section. Fire protection in various types of structures can be found in [5] or using flame retardants described here [6][7][8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To increase the fire resistance of structure is considered to do various methods of protection of beam section. Fire protection in various types of structures can be found in [5] or using flame retardants described here [6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…Analysing fire loaded structures 4 main groups of problems have to be solved: -Selection of the design fire scenario to describe the real expected load -Determination of the corresponding design fire -Calculation of temperature development in structural elements -Calculation of the mechanical behaviour of structure subjected to fire Various researcher were focused on the structural response under the fire load. Louter et al [3] conducted research on structural response of fire-exposed laminated glass beams, Vedrtnam et al in [4] studied the compressive behaviour of sustainable cement-based composites under one-hour of direct flame exposure, Bedon studied fire resistance of in-plane compressed log-house timberwalls with partial thermal insulation in [5]. Behaviour and design of eccentrically loaded hot-rolled steel SHS and RHS stub columns at elevated temperatures was described in [6], Non-linear analysis of composite beam subjected to fire was done in [7].…”
Section: Introductionmentioning
confidence: 99%
“…Vedrtnam et al [22]. studied the response of cement-based composites under direct flame conditions, demonstrating improvement in the residual compressive strength compared to conventional concrete after the thermal exposure.…”
Section: Global Contextmentioning
confidence: 99%
“…The inclusion of polymer bers, for instance, has shown promise in preventing thermally induced explosive spalling, where the bers melt around 170 ºC, creating pathways for steam migration and reducing pore pressure within the matrix [10]. Prior research has demonstrated that incorporating processed PET residuals can enhance the re retardancy of concrete samples [11]. Nevertheless, challenges persist in achieving superior post-re load-bearing capacity in re-resistant concrete.…”
Section: Introductionmentioning
confidence: 99%